Correlation between domain structure dynamics and electromechanical behavior in Sn-doped BaTiO3 - Kraft, Viktoria; Cicconi, Maria Rita; Pal, Subhajit; Kuhfuß, Michel; Khansur, Neamul Hayet; Martin, Alexander; Kimura, Koji; Takabayashi, Yasuhiro; Mibu, Ko; Hayashi, Koichi; Briscoe, Joe; Webber, Kyle Grant (Journal of Materials Chemistry C, 2025)
Lead-free photoferroelectrics are promising for multimodal energy conversion systems that can harvest diverse ambient energy sources, including light and mechanical vibrations. When multiple physical phenomena are coupled within a single material, the ferroelectric, piezoelectric, and photoresponsive properties are strongly governed by the ferroelectric domain structure and domain wall mobility. To lay the groundwork for understanding such complex couplings, this study focuses on isolating and investigating the influence of the domain structure in Sn-doped BaTiO3(BaSnxTi1−xO3) on its small-signal electromechanical behavior. Rayleigh analysis was carried out to study domain wall mobility as a function of Sn content up to 11 mol%, revealing the highest irreversible contributions around 11 mol% Sn. Additionally, domain types were investigated with spatially resolved Raman spectroscopy and piezoresponse force microscopy, and correlated with electromechanical properties. These results demonstrate that Sn doping modifies the domain sizes and shapes, impacting domain wall mobility and dielectric response. Understanding domain structure dynamics in relation to electromechanical behavior is essential for optimizing coupled photoferroelectric properties.
CRIS-Team Scopus Importer:2025-12-12

Feasibility of Powder-Based High-Throughput Synthesis for Ceramics Development: Case Study on the Influence of Calcination Temperature in BiFeO3-BaTiO3 - Eckstein, Udo; Kuhfuß, Michel; Fey, Tobias; Webber, Kyle Grant (Advanced Engineering Materials, 2024)
Recent advances in machine learning capabilities have increased interest in materials research to improve the efficiency of materials discovery and optimization as well as to better understand the underlying phenomena responsible for the observed physical properties. While combinatorial chemistry and compositional engineering is well established in the development of pharmaceutical and chemical products, its use in the field of bulk functional polycrystalline ceramics is far from mature. In this work, a critical review of a high-throughput powder-based dispensing system is provided and the challenges involved with the transition from a conventional, human resources intensive workflow to a fully automated process are highlighted. Based on the lead-free piezoelectric BiFeO3–BaTiO3 binary system, the applicability and robustness of high-throughput engineering is investigated to increase data point density in phase diagrams, including the composition variations of the resulting materials. This work presents 16 different BiFeO3–BaTiO3 compositions at four different calcination temperatures, both demonstrating the potential of the system. This is coupled to automated crystal structure analysis, which will be used to investigate the role of calcination temperature on the resulting compositions at room temperature.
CRIS-Team Scopus Importer:2024-03-01
Keywords: combinatorial chemistry; compositional engineering; high-throughput XRD; powder dispensing; solid state reactions; structural characterizations

Influence of grain size on electromechanical properties of (Ba,Ca)(Zr,Ti)O3: A multiscale analysis using spark plasma sintering and aerosol deposition - Maier, Juliana; Kuhfuß, Michel; Urushihara, Daisuke; Gadelmawla, Ahmed; Khansur, Neamul Hayet; Hall, David; Algueró, Miguel; Martin, Alexander; Kakimoto, Ken-ichi; Webber, Kyle Grant (Ceramics International, 2024)
The piezoelectric and ferroelectric properties of aerosol deposited (AD) thick ceramic films are significantly reduced in comparison to bulk materials, which is assumed to be largely related to the nanometer-sized grains (∼0.01 μm) observed in the resulting microstructures. This work, therefore, focuses on understanding the role of grain size in electromechanical properties within the range of AD films based on Ba0.85Ca0.15Zr0.1Ti0.9O3 (BCZT). In a comprehensive compilation of the piezoelectric constant (d33) of samples from various studies the grain size dependency of the d33 was shown for the lead-free ferroelectrics BCZT, BaTiO3, and (K,Na)NbO3. In this, it can be seen that no BCZT sample with a grain size below 0.4 μm was analyzed regarding their d33 before, thereby leaving a gap to the grain size of AD films. In this study, the grain size of ceramic bulk samples was varied using spark plasma and conventional sintering (0.1 μm – 11 μm) and their properties compared to those of AD films. To enable the fabrication of bulk samples in the same range as AD films, a hydrothermal powder with an average particle size of 0.075 μm was synthesized. A continuous increase of the permittivity, the polarization, and the piezoelectric coefficient was observed through grain size increase. These results suggest that the grain size of AD films needs to be enhanced to improve their properties. Importantly, the insights of this multiscale analysis on the grain size can help to tailor also the properties of other BCZT films and bulk samples.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Aerosol deposition; Barium calcium zirconium titanate; Grain size; Lead-free; Spark plasma sintering; Synchrotron

Influence of tin concentration on the electronic structure and ferroelectric behavior of barium titanate: Experimental and first-principles insights - Kraft, Viktoria; Spreafico, Samuele; Cicconi, Maria Rita; Kuhfuß, Michel; Mibu, Ko; Kimura, Koji; Hayashi, Koichi; Balanov, Vasilii A.; Bai, Yang; Khansur, Neamul Hayet; Meyer, Bernd; Webber, Kyle Grant (Journal of Applied Physics, 2025)
To meet the growing demand for energy, multimodal energy conversion systems, such as photoferroelectrics, are receiving increased attention. Among these, oxide perovskites like Sn substituted barium titanate exhibit enhanced piezoelectric coefficient and dielectric permittivity at room temperature compared to the parent composition. This study investigates whether these enhancements originate from intrinsic Sn incorporation or extrinsic contributions. Additionally, the impact of Sn on the electronic bandgap is examined, which is critical for multifunctional applications. A combined experimental and first-principles approach is employed to systematically analyze different Sn concentrations (0-12.5 mol. % Sn), focusing on B-site ordering in BaTiO3. The experimental analysis includes dielectric and ferroelectric measurements, diffuse reflectance spectroscopy, and photoconductivity measurements for bandgap estimations. Computational screening reveals that Sn ions repel each other and preferentially adopt second neighbor B-site positions along the Ti-O-Ti bond. While the bandgap shows minimal changes (meV range), spontaneous polarization and polarization hysteresis decrease significantly with increasing Sn content. The experimentally observed increase in piezoelectric response is thus attributed primarily to extrinsic effects on the meso- and macroscales from the domain structure and the coexistence of phases around 11 mol. % Sn, rather than to intrinsic incorporation of Sn into the perovskite lattice.
CRIS-Team Scopus Importer:2025-09-19

In situ electric field-dependent structural changes in (Ba,Ca)(Zr,Ti)O3 with varying grain size - Kuhfuß, Michel; Maier, Juliana; Hall, David A.; Xie, Bingying; Kleppe, Annette K.; Martin, Alexander; Kakimoto, Ken-ichi; Khansur, Neamul Hayet; Webber, Kyle Grant (Journal of Applied Physics, 2024)
The functional properties of piezoelectric ceramic materials, such as barium titanate, are highly dependent on grain size. Lead-free polycrystalline Ba0.85Ca0.15Zr0.1Ti0.9O3 (BCZT) samples were prepared with a combination of the hydrothermal method and spark plasma sintering to achieve grain sizes from 100 nm to 10 μm by varying the maximum sintering temperature. In this range, a transition from a nearly linear dielectric to a ferroelectric response can be seen in macroscopic electromechanical measurements, demonstrating the importance of grain size on functional properties in BCZT. Furthermore, in situ electric field-dependent synchrotron x-ray diffraction measurements were performed to quantify the intrinsic and extrinsic strain contributions and their variations with grain size. At lower grain sizes, the data revealed a significant loss of extrinsic contributions in the piezoelectric behavior, limiting the response to intrinsic contribution associated with lattice strain. For BCZT, a critical grain size between approximately 0.08 and 0.18 μm is proposed, below which no piezoelectric response was observed.
CRIS-Team Scopus Importer:2024-05-17

Novel Sol-Gel Synthesis Route for Ce- and V-Doped Ba0.85Ca0.15Ti0.9Zr0.1O3 Piezoceramics - Marques, Larissa S.; Weichelt, Michelle; Kuhfuß, Michel; Rambo, Carlos R.; Fey, Tobias (Materials, 2024)
To meet the current demand for lead-free piezoelectric ceramics, a novel sol-gel synthesis route is presented for the preparation of Ba0.85Ca0.15Ti0.9Zr0.1O3 doped with cerium (Ce = 0, 0.01, and 0.02 mol%) and vanadium (V = 0, 0.3, and 0.4 mol%). X-ray diffraction patterns reveal the formation of a perovskite phase (space group P4mm) for all samples after calcination at 800 °C and sintering at 1250, 1350, and 1450 °C, where it is proposed that both dopants occupy the B site. Sintering studies show that V doping allows the sintering temperature to be reduced to at least 1250 °C. Undoped BCZT samples sintered at the same temperature show reduced functional properties compared to V-doped samples, i.e., d33 values increase by an order of magnitude with doping. The dissipation factor tan δ decreases with increasing sintering temperature for all doping concentrations, while the Curie temperature TC increases for all V-doped samples, reaching 120 °C for high-concentration co-doped samples. All results indicate that vanadium doping can facilitate the processing of BCZT at lower sintering temperatures without compromising performance while promoting thermal property stability.
CRIS-Team Scopus Importer:2024-07-19
Keywords: (BCZT); Ba; cerium; doping; lead-free piezoceramics; sol-gel; vanadium

Study on Growth of Tungsten Bronze Phase from Niobate Perovskite Ceramics in Controlled Atmosphere for Photoferroelectric Applications - Shi, Xi; Bai, Yang; Wichmann, Christoph; Moritz, Michael; Kuhfuß, Michel; Papp, Christian; Khansur, Neamul Hayet (Advanced Electronic Materials, 2023)
Recent research has found that by introducing A-site deficiency into Ba/Ni co-doped (K,Na)NbO3 ABO3-type perovskite, a beneficial interface for photoferroelectric applications is formed between the perovskite and tungsten bronze (TB) phases. To date, such an interface is formed only spontaneously, and the growth mechanism of the TB phase in the perovskite phase is unclear. This work investigates controlled interface formation using KNBNNO (K0.50Na0.44Ba0.04Ni0.02Nb0.98O2.98) annealed at different temperatures for different durations, and in various atmospheres. Structural, microstructural, and chemical analyses suggest that vacuum, N2, and O2 atmospheres promote the growth of the TB phase from the sample surface, of which the thickness increases with annealing temperature and duration. In contrast, annealing in air does not promote such growth due to lower evaporation of K and Na. Among all atmospheres, the growth starts the earliest, i.e., at 800 °C, in vacuum compared to that as late as 1000 °C in O2. The association of growth of the TB phase with the degree of alkali volatilization that is dependent on the atmosphere, and that with the resultant variation in diffusion rate, uncovers the formation mechanism of the beneficial interface that may also be applicable to other KNN-based materials for advanced photoferroelectric applications.
CRIS-Team Scopus Importer:2023-12-15
Keywords: (K; Na)NbO3 perovskite; photoferroelectric applications; tetragonal tungsten bronze phase

Temperature-dependent electromechanical response of BaTi1₋xSnxO3: Analysis of reversible and irreversible contributions - Kraft, Viktoria; Eckstein, Udo; Kuhfuß, Michel; Khansur, Neamul Hayet; Marlton, Frederick P.; Mullens, Bryce; Martin, Alexander; Hayashi, Koichi; Webber, Kyle Grant (Journal of the American Ceramic Society, 2025)
The increasing demand for efficient, multifunctional energy conversion systems has sparked interest in light-active polar perovskite oxides. These materials offer structural flexibility and chemical tunability, making them promising candidates for multimodal energy harvesting. In particular, photoferroelectrics enable the simultaneous harvesting of thermal, light, and mechanical energy. However, mostly room temperature properties have been studied, leaving a critical gap in understanding their behavior under varying thermal conditions. This study investigates the electromechanical properties in conjunction with crystallographic changes of photoferroelectric BaTi1₋xSnxO3 across a temperature range of −150°C to 150°C. Increasing Sn content reduces tetragonal distortion, shifts phase transition temperatures, and induces a multi-phase region at higher concentrations. As a result, temperature-dependent small-signal measurements show changes in dielectric and piezoelectric responses, with a trend toward relaxor-like behavior at higher Sn levels. Rayleigh analysis of stress amplitude-dependent piezoelectric coefficient reveals enhanced properties at specific compositions, for example, 7 mol% Sn) and temperatures, attributed to an optimal balance of reversible and irreversible contributions. Further, Sn doping appears to improve thermal stability by reducing irreversible contributions. These results provide significant implications for optimizing photoferroelectric BaTiO3 by influencing material properties through Sn doping for various applications, including energy harvesting.
CRIS-Team Scopus Importer:2025-10-17
Keywords: barium titanate; electromechanical properties; ferroelectricity/ferroelectric materials; low temperature; piezoelectric materials/properties

Temperature-dependent residual stress in aerosol-deposited barium titanate films - Kuhfuß, Michel; Eckstein, Udo; Urushihara, Daisuke; Asaka, Toru; Xie, Lixu; Martin, Alexander; Kakimoto, Ken ichi; Webber, Kyle Grant (Ceramics International, 2025)
Aerosol deposition is a promising technique for preparing thick, dense ceramic films on various substrates at room temperature. However, the resulting microstructure shows disadvantages for certain applications; for instance, defects and residual stresses are, together with the nanocrystalline grains, responsible for the low functional properties of aerosol-deposited films, limiting their usability for applications such as piezoelectric energy harvesting. As such, this study investigates the relaxation of aerosol deposition-induced defects and residual compressive stress during annealing. Barium titanate films with a 10–15 μm thickness are sprayed on stainless steel substrates as a model material system. While as-deposited films display linear dielectric behavior, ferroelectricity can partially be recovered by annealing up to 600 °C. This is proposed to be connected with a reduction in compressive residual stress that is directly observed using in situ temperature-dependent X-ray diffraction. Above 250 °C, a transition from compressive towards tensile stress can be found, which is caused by thermal expansion and an observed shrinkage of the film. This shrinkage is proposed to be connected to a recombination of defects, e.g., oxygen vacancies. After annealing up to 700 °C, the residual stress is permanently reduced from −420 MPa to −320 MPa, and defects, such as the non-crystalline grain boundary areas observed in transmission electron microscopy, are partially relaxed. However, annealing temperatures above 500 °C could be responsible for reintroducing additional compressive stress due to the thermal expansion mismatch between film and substrate.
CRIS-Team Scopus Importer:2025-10-24
Keywords: BaTiO; Dielectric properties (C); Films (A); X-ray methods (B)